Non-smooth integral sliding surface based control for systems with mismatched disturbances - Goyal J.K.; Sachan A.; Prabha N.A.; Kamal S.; Chauhan A.K.; Ghosh S.; Bandyopadhyay B.; Xiong X. (My University, 2025)
This paper addresses the problem of traditional sliding mode control design subject to the mismatched disturbance. Existing methods fail to provide an efficient and simple solution. To counteract the unmatched disturbance in the system, a new sliding mode control strategy based on a non-smooth integral sliding manifold is proposed. The proposed sliding manifold has two important features. First, it acts like a reduced order disturbance observer since it estimates the mismatched disturbances by itself without any requirement of an additional observer design. Secondly, the system always starts from the sliding surface, hence, there is no reaching phase dynamics. Thus, the system trajectory is insensitive towards the disturbance from the initial point. The proposed method is tested on a coupled tank system to demonstrate its effectiveness. Both the simulation and experimental results are provided. © 2023